CMOS Fabricated Large Array of Free Standing Substrate-Less Photonic Crystal Cavities for Biosensing Applications - Kumar Saurav; Sulakshna Kumari; Nicolas Le Thomas (IEEE Photonics Journal, 2017)
In this paper, we present a methodology to postprocess a large array of a few hundred nanometer thin photonic membranes that were fabricated using complementary metal-oxide-semiconductor (CMOS) technological platform. The postprocessing results in local removal of the silicon substrate and of the buried oxide, which provides a free access from both side of the photonic structures. The membranes are patterned with photonic crystal cavities by deep ultraviolet lithography. We show that the proposed process is compatible with the integration of micrometer-sized SU8-based polymer waveguides. These polymer waveguides, together with high index contrast adiabatic nanometer-sized silicon inverted tapers, act as spot size converters. In addition, although a significant number of processing steps is required to achieve such free-standing substrate-less cavities, the quality (Q) factors of the cavities that is of the order of a few thousand remains unaffected.